Fertility index of industrial polluted land and plant response to heavy metal contamination - Mindari, Wanti; Sasongko, Purnomo Edi; Aditya, Haidar Fari; Karam, Daljit Singh; Masri, Intan Nadhirah (Malaysian Society of Soil Science, 2023)
Industrial waste in the Sidoarjo Regency, Java, Indonesia has polluted the agricultural land around it. The high level of heavy metal pollution in these fields affects the physical, chemical, and biological characteristics of the soil and plant growth. This study aimed to examine the soil fertility index (SFI) of four agricultural plots of land around the paper, pharmaceutical, animal feed, and leather industries in the Sidoarjo region and the response of food crops to heavy metal contamination. The research was carried out in two stages, Stage (1): Evaluation of the soil fertility index (SFI) based on physical, chemical, and biological characteristics of the main soils; Stage (2): The response of rice plants and maize to heavy metal contamination. The SFI value is derived from the minimum soil chemical-physical-biological characteristic indicator values which include pH, EC, cation exchange capacity (CEC), K, Na, Ca, Mg, heavy metals (Fe, Mn, Zn, Cu, Pb, Hg, Cd) clay, and C-organic soils. The results showed that the value of the soil fertility index of agricultural land around the industries in the Sidoarjo area was low to moderate. The value of SFI is obtained through factor analysis of highly correlated soil features. The main factors determining the low value of SFI are soil pH, soil texture, and heavy metal content of Pb, Cd, Fe, and Zn. Therefore, it is not advisable to cultivate rice and corn in the region due to the significant uptake of high levels of heavy metal elements by these plants, which not only compromises their growth but also human health.